Value education: essential tool for socio-political and economic development in Nigeria (2017)
The neglect of ethical values, which should form the substratum of any good education, has led to ineffectual, decadent, and poor learning. The duty of every society is to pass on the values enshrined in its scriptures and philosophical texts to each generation, in order, that the spirit of its culture lives on. Findings showed that a society with no required values cannot witness peace, growth and development. What is obtainable in the Nigeria society today are flagrant abuse of office, high and low profile corruption, poor attitude to work, gross misconduct, flair for frivolity and materialism, dependency of the Judiciary, lack of trust and so on. It was discovered that in planning for good values and objectives, the teachers and students, leaders and followers will have to cooperate and work together as a team, an indivisible entity. The purpose of education is to strengthen character in the younger generation which would provide solution to the problems facing Nigeria as a nation. This can only be achieved when education is value-oriented. The paper, therefore, recommends the core values of democracy which promotes a secure physical, emotional and political locus within the society. There is a need for a widespread renewal of individual commitment to an active life of principle and societal values like truth, right action, love, peace and non violence means of getting things done. As well, there is a need for better preparation of teachers as values educators.